Analysis of Metaphorical Expressions Used in Johnny Cashs’ Song Lyrics - Juliana Juliana; Risa Anggraini; Ardytha Ardytha (Edumaspul: Jurnal Pendidikan, 2023)
This research explores Johnny Cash's song lyrics using George Lakoff's metaphor theory. It aims to understand the metaphorical expressions in Cash's song lyrics by analyzing their recurring themes and their connection to the socio-cultural context of the artist's era. The research includes identify metaphorical expressions and examine thematic motifs, the cultural and historical context that influenced the author's use of metaphors. The research also examined the influence of metaphorical language on the narrative depth and affective impact of Cash's compositions. Grounded theory in established metaphor analysis and the function of metaphor in artistic expression, the research expands upon the cognitive linguistic perspective by situating the analysis within Lakoff's theory. It gains insight into how metaphors communicate complex emotions, abstract ideas, and societal contemplations in Cash's lyrics. The research uses a systematic methodology to select songs and employs techniques for identifying metaphors based on Lakoff's theoretical framework. Thematic analysis is used to identify recurring patterns within the metaphorical expressions, while cultural contextualization helps understand the factors that shaped Cash's imaginative use of metaphors. This research had significant contribution to musicology, literary studies, and cultural analysis. By analyzing the metaphorical depth of Cash's lyrics from Lakoff's theory, it provides an original perspective on the artist's thought process and enhances the understanding of the lasting importance and thematic complexity of his contributions in contemporary music.